Development of new code for optical code division multiple access systems - Hilal Adnan Fadhil (School of Computer and Communication Engineering, University Malaysia Perlis, 2010)
In this thesis, multiple access and multiplexing issues are focused on through studies performed at the physical layer. In this thesis, new code families for spectral- amplitude coding systems to enhance the performance of OCDMA systems have been proposed.